2021
DOI: 10.1111/eci.13735
|View full text |Cite
|
Sign up to set email alerts
|

Enoxaparin for thromboprophylaxis in hospitalized COVID‐19 patients: The X‐COVID‐19 Randomized Trial

Abstract: Background It is uncertain whether higher doses of anticoagulants than recommended for thromboprophylaxis are necessary in COVID‐19 patients hospitalized in general wards Methods This is a multicentre, open‐label, randomized trial performed in 9 Italian centres, comparing 40 mg b.i.d. versus 40 mg o.d. enoxaparin in COVID‐19 patients, between April 30 2020 and April 25 2021. Primary efficacy outcome was in‐hospital incidence of venous thromboembolism (VTE): asymptomatic or symptomatic proximal deep vein thromb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(76 citation statements)
references
References 35 publications
1
67
1
1
Order By: Relevance
“…This is in agreement with previous prospective studies, the HEP-COVID, and X-COVID-19 trials showing a low prevalence of asymptomatic proximal DVT of 0% to 2.9% among acutely ill medical patients. 14,17,[30][31][32] In the ICU, we did not find the elevated (5%-23%) risks found by previous prospective studies. [33][34][35][36][37] Our trial has several strengths.…”
Section: Ta B L E 1 (Continued)contrasting
confidence: 98%
“…This is in agreement with previous prospective studies, the HEP-COVID, and X-COVID-19 trials showing a low prevalence of asymptomatic proximal DVT of 0% to 2.9% among acutely ill medical patients. 14,17,[30][31][32] In the ICU, we did not find the elevated (5%-23%) risks found by previous prospective studies. [33][34][35][36][37] Our trial has several strengths.…”
Section: Ta B L E 1 (Continued)contrasting
confidence: 98%
“…confirming the de novo nature of the pulmonary thrombi (Morici et al, 2021). A cohort study showed an increasing prevalence of PE with increasing D-dimers, with a 10-fold elevation strongly predictive of PE (Perera et al, 2021).…”
Section: Intravascular Coagulopathymentioning
confidence: 74%
“…An increase in bleeding was also observed [ 69 , 70 , 71 ]. The studies we discussed [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ] and the available meta-analyses [ 62 , 63 , 64 , 65 , 66 ] revealed the need for a tailored anticoagulant therapy. Heparin was shown to reduce mortality both at prophylactic and therapeutic dosages; however, an increase in bleeding was reported [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although underpowered, the analysis of 183 patients showed no deep vein thrombosis in COVID-19 hospitalized patients in both groups; however pulmonary embolism was observed only in the prophylactic dose group (six patients). No major bleeding and thrombocytopenia events were reported [ 61 ].…”
Section: Evidence Of Heparin Use In Covid-19 Acute Illnessmentioning
confidence: 99%